Development of Science Process Skill (KPS) Assessment in POE (Predict, Observe and Explain) Learning in Acid-Base Titration - Gunawan, Ricky; Feronika, Tonih; Saridewi, Nanda (LAVOISIER: Chemistry Education Journal, 2023)
This research was about the development of an instrument assessment of skills the process of science in learning POE (predict, observe and explain) in titration acid bases, in significance this assessment instruments contains aspect of science process skills i.e. aspect of observation, classification, interpretation, prediction, making the question, hypotheses, design experiments, using tools and materials, applying concepts and communicate that categorized on stage learning POE. This assessment instruments was developed to the matter titration acid bases based on the analysis of KD in 2013 curriculum. Research methodology used is DDR (design and development research). The assessment is an instrument developed through 3 stages, namely: (1) study design (concept of a development), (2) stages of development, and (3) stages of evaluation. The purpose of this research is to produce an instrument for skill process of science in learning POE on titration acid base. This research include the development and products finally tested to 22 respondents by 22 students class XI MA Dharma Karya UT, South Tangerang. Based on the data so can be concluded this instrument has characteristics: assessment is organized by using stage POE, now housed assessment ten aspects skill the process of science, now housed assessment discourses whose characteristics are in accordance with matter or the concept of titration acid bases and environment students as well as this assessment use rubrics with scales 0-4 for diplomatic learning can be assessed in detail. Based on the percentage the average from the validation the people of, pilot products and chief responsi teachers, products this assessment get the percentage an average of 84,71 % and into category is very good.